Analisis Implementasi Pembangunan Partisipatif dalam Program Kota Tanpa Kumuh ( KOTAKU ) Studi Komparatif : Desa Bligo Kecamatan Candi dan Desa Jiken, Kecamatan Tulangan, Kabupaten Sidoarjo, Jawa Timur (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2018)
The phenomenon of slum settlements has been increasingly occurring in Indonesia. President of Indonesia, Joko Widodo having a vision to implement the development program known as Kota Tanpa Kumuh. This program is conducted in more than 100 districts in Indonesia. However, Sidoarjo regency becomes the public spotlight due to its development. Unfortunately, there are two slum villages having different development results. Bligo becomes a successful village in establishing development. Meanwhile, Jiken Village fails in achieving the development. Although two villages have same characteristics and regional regulatory support, it’s not sufficient to support the success of development. This research applying qualitative descriptive approach to obtain the importance of participation in development process. It’s also important to explain the forms and the factors that influence participation.With applying the Eight Rungs of Citizen Participation, can determine that Bligo village is in citizen control, in which the community plays a full role in program implementation. Contrastingly, Jiken village only in the  of Informing stage, where the public only get information from the government without any community empowerment. The participation is crucial to the success of the development program. This is due to the existence of self-belonging exerting the ability to create sustainable development achievement